Alterations and Potential Applications of Gut Microbiota in Biological Therapy for Inflammatory Bowel Diseases - Pu, Dan; Zhang, Zhe; Feng, Baisui (Frontiers in Pharmacology, 2022)
Inflammatory bowel disease (IBD), including Crohn's disease and ulcerative colitis, is a chronic immune-mediated inflammatory disorder of the gastrointestinal tract that is closely associated with dysbiosis of the intestinal microbiota. Currently, biologic agents are the mainstream therapies for IBD. With the increasing incidence of IBD, limitations of biologic agents have gradually emerged during treatment. Recent studies have indicated that gut microbiota are highly correlated with the efficacy of biologic agents. This review focuses on alterations in both the components and metabolites of gut microbiota during biological therapy for IBD, systematically summarises the specific gut microbiota closely related to biological efficacy, and compares current predictive models for the efficacy of biologics, while highlighting the predictive value of intestinal microbiota. Based on the mechanistic analysis of faecal microbiota transplantation (FMT) and biologic agents, a new therapeutic strategy, comprising a combination of FMT and biologics, has been proposed as a promising treatment for IBD with improved efficacy.